Proteins of the Inner Membrane of Escherichia coli: Changes in Composition Associated with Anaerobic Growth and Fumarate Reductase Amber Mutation - Spencer, Margaret E. (1974)
The inner membrane fractions of Escherichia coli grown anaerobically and aerobically were isolated, and their proteins were compared by electrophoresis in polyacrylamide gels. To maximimize the differences between the preparations, the anaerobic cultures were grown on complex medium with added glucose, but glucose was omitted from the aerobic cultures to prevent catabolite repression. The pattern of bands in the two types of preparation differed considerably, and changes in approximately 20 components were observed. In particular, the band identified as succinate dehydrogenase in aerobic preparations was greatly reduced in anaerobic preparations. Mutants lacking fumarate reductase were isolated, and inner membrane preparations of an frd amber mutant were deficient in a major component of 75,000 daltons and possibly a minor one of 87,500 daltons. The former was also present in greater amounts in anaerobic preparations and could represent a fumarate reductase subunit.